HUBUNGAN INDONESIA AMERIKA DI MASA OBAMA : dari Kerja Sama Antiteroris sampai Penggalangan Demokrasi - Siswanto Siswanto (Pusat Penelitian Politik, 2011)
This paper is to analyze the USA Indonesia relationship in the period ofObama presidency since the relationship between two countries has a very greatpotency and opportunity to be more improvable As we all recognizethat President Obama has a special relation with Indonesia because ofhe lived through his childhood in Indonesiaeventhough there will be no guarantee that will become the main reason in improving better relationship sinceit is related to many political variables As conclusion this paper argues that the prospect of the USA Indonesiarelationship basically depends on how the two countries implement Comprehensive Partnership Agreement as wellas possible and how both sides give serious attention to improve better bilateral relationship